2011
DOI: 10.1590/s1679-78252011000300009
|View full text |Cite
|
Sign up to set email alerts
|

The natural frequencies of composite Profiled Steel Sheet Dry Board with Concrete infill (PSSDBC) system

Abstract: This paper aims to measure natural frequencies of Profiled Steel Sheet Dry Board (PSSDB) with Concrete infill (PSS-DBC) system. For this purpose, experimental tests by estimation of Frequency Response Function (FRF) and a numerical method by development of Finite Element Model (FEM) are used. The connection stiffness between Peva45 as Profiled Steel Sheet (PSS) and different concrete grades of 25 (C25), 30 (C30), and 35 (C35) are measured by pushout tests to be used in the FEM. The effect of presence of concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Gandomkar et al [18] estimated damping ratios of bare PSSDBC panels with such characteristics as: width and length of 795 mm and 2400 mm respectively, and thicknesses of 0.8 mm and 18 mm respectively for PSS and DB, 200 mm screw spacing, and concrete grade of 30 (C30) where the panels were located on pin-roller end supports. Damping ratios of 2.90%, 1.52%, 0.83%, and 2.54% were found for the first four vibration modes, respectively.…”
Section: Dampingmentioning
confidence: 99%
See 2 more Smart Citations
“…Gandomkar et al [18] estimated damping ratios of bare PSSDBC panels with such characteristics as: width and length of 795 mm and 2400 mm respectively, and thicknesses of 0.8 mm and 18 mm respectively for PSS and DB, 200 mm screw spacing, and concrete grade of 30 (C30) where the panels were located on pin-roller end supports. Damping ratios of 2.90%, 1.52%, 0.83%, and 2.54% were found for the first four vibration modes, respectively.…”
Section: Dampingmentioning
confidence: 99%
“…The connection between Peva45 and concrete as an infill in trough of Peva45 is also a partial interaction problem. Gandomkar et al [18] focused on finding the connection stiffness between Peva45 and concrete with different grades of C25, C30, and C35 by push-out tests where covering was chosen as plywood. The shear stiffness of this connection was obtained as 386 kN/mm and 417.60 kN/mm respectively for C30 and C35 where spacing between the springs was considered as 200 mm.…”
Section: Structural Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The geopolymer concrete, in addition to being eco-friendly is high strength and expected to improve the structural performance of the PSSDB floor system in terms of stiffness and strength. Previous research involving normal concrete infill in PSSDB floors have been reported in Shodiq (2004), , Seraji et al (2013), and Gandomkar et al (2011 and. Shodiq (2004) has demonstrated that the stiffness and strength of the PSSDB floor system with normal concrete infill is 20.2% and 61.0% higher than the one without infill.…”
Section: Introductionmentioning
confidence: 95%
“…The PSSDB in its original form was envisaged by Wright et al (1989) as an alternative to the traditional timber plank and joist floor system in the United Kingdom. Research works have since been conducted on the PSSDB system in its applications as flooring, roofing, and walling units (Ahmed et al (2000 and, , , 2005, Akhand et al (2004), Gandomkar et al (2011Gandomkar et al ( , 2012Gandomkar et al ( , 2013aGandomkar et al ( and 2013b, Seraji et al (2012)). This paper reports on the research work conducted on the PSSDB floor system introducing geopolymer concrete (Abdullah et.…”
Section: Introductionmentioning
confidence: 99%